Implementation of Hybrid Learning to Maintain the Quality of Learning in Fostered MTs During the Covid-19 Pandemic - Pathurohman Pathurohman; Michael Berger; Guri Michael (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2022)
During the Covid-19 pandemic, the education sector was also greatly affected, because in order to stop the spread of this corona all students and teachers studied from home, which was suddenly carried out without any preparation at all. The unpreparedness of all elements in education is a big obstacle, changing the way of teaching and learning from face to face or offline (outside the network) to online (in the network) requires readiness from all elements, starting from the government, madrasas, teachers, students and parents. The government relaxed the education assessment system according to emergencies as long as learning can continue without having to be burdened with achieving competence. Many teachers teach by utilizing existing technology. The purpose of this study is to describe the implementation of the implementation of learning strategies through the collaboration of WAG (Whatsapp Group) and Offline during the Covid-19 pandemic emergency. This research is divided into two stages, each stage has different characteristics from one another. From data collection, data analysis, and discussion results, it is known that the implementation of learning strategies through WAG (Whatsapp Group) collaboration and offline was carried out to maintain the quality of the teaching and learning process during the Covid-19 Pandemic at MTs assisted by Malang Regency. The implementation of Cycle I focused on the necessary administrative preparations while the implementation of Cycle II focused on formulating decrees on the administration of learning activities, circulars for meetings with parents/guardians of students to socialize the WAG (Whatsapp Group) and offline collaboration models.